Implementasi Hadist Tasamuh dalam Bermasyarakat - Ikhsan Huzali (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Tolerance in Islam is an interesting study, this is based on the very difficulty of finding the equivalent of the word Tolerance in the Al-Qur'an and Hadith. Differences in understanding the meaning of tolerance form the basis of understanding Pluralism. This article is to examine the meaning of tolerance in the hadith as the second source of the Islamic religion, using a social approach. This article finds that Tolerance in the Hadith is combined with the word tasamuh with the meaning or samahah of this word basically meaning al-jud (Glory). Or sa'at sadr (open-minded) and tasahul (friendly, forgiving). Islam itself is a religion that makes tolerance the most important part, this attitude is more widely applied in the area of ​​social interaction as shown by the attitude of the Prophet Muhammad. against non-Muslims at the time he was still alive. An attitude of tolerance in religion is respecting other religious beliefs by not being syncretic, namely by equating other religious beliefs with Islamic beliefs themselves, practicing one's own beliefs and worship. The attitude of tolerance also cannot be understood separately from the framework of the Shari'a, because if it happens, it will give rise to misunderstandings of meaning which result in a mixture of what is right and what is false. The teaching of tolerance is something that is inherent in the principles of Islamic teachings as found in faith, Islam and ihsan.